Basic income: economy and psychology - Hevlych, Larysa; Hevlych, Ivan; Dutova, Natalia (Research Papers in Economics and Finance, 2020)
Basic income is a social idea appealing to humanist philosophers and politicians. Numerous experiments on the introduction of the concept of basic income occurred in countries with varying degrees of economic development. Surveys are being conducted around the world on the need to introduce basic income. Dynamics of economic processes and social sentiment in individual countries require generalisation of modern factors influencing the possibility of practical implementation of the concept of basic income. This paper studies the economic and psychological factors for supporting the idea of basic income in terms of its practical implementation, analyses the interpretation of the UBI idea by various researchers and provides a characteristic of the modern vision of basic income. The arguments for and against the practical implementation of this idea with their structuring in the following directions are formed and considered: influence on the economy, change of social relations and possibility of practical realisation. The authors presentgeneralised results of the experiments on the introduction of basic income from the 1960s to the present day in South America, Africa, Europe, Asia, as well as the results of the poll and referendum on the introduction of basic income in Switzerland in 2016.